2009
DOI: 10.1172/jci37878
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 drives secondary autoimmunity in patients with multiple sclerosis, following therapeutic lymphocyte depletion with alemtuzumab (Campath-1H)

Abstract: Phase II clinical trials revealed that the lymphocyte-depleting humanized monoclonal antibody alemtuzumab (Campath-1H) is highly effective in the treatment of early relapsing-remitting multiple sclerosis. However, 30% of patients develop autoimmunity months to years after pulsed exposure to alemtuzumab, usually targeting the thyroid gland and, more rarely, blood components. In this study, we show that autoimmunity arose in those patients with greater T cell apoptosis and cell cycling in response to alemtuzumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
234
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(244 citation statements)
references
References 48 publications
8
234
0
2
Order By: Relevance
“…The results of a phase II clinical trial with the lymphocyte-depleting humanized monoclonal antibody alemtuzumab (Campath-1H) show that it is highly effective in the treatment of early relapsing-remitting MS (87). A single pulse of treatment results in rapid, profound and prolonged lymphopenia.…”
Section: Ms and Autoimmune Diseasesmentioning
confidence: 99%
“…The results of a phase II clinical trial with the lymphocyte-depleting humanized monoclonal antibody alemtuzumab (Campath-1H) show that it is highly effective in the treatment of early relapsing-remitting MS (87). A single pulse of treatment results in rapid, profound and prolonged lymphopenia.…”
Section: Ms and Autoimmune Diseasesmentioning
confidence: 99%
“…We have shown that pre-treatment serum interleukin-21 may serve as a biomarker for the risk of developing autoimmunity for months to years [28].…”
Section: Autoimmunitymentioning
confidence: 99%
“…Changes in T-cell properties are also seen at the individual cell level after alemtuzumab administration [33]. In vitro Tcell proliferative potential is substantially increased 3 months after therapy compared to pretreatment.…”
Section: Ahsct Mechanism Of Action: the Immunosuppression Hypothesismentioning
confidence: 99%